Civil Unrest and Herding Behavior: Evidence in an Emerging Market - Espinosa-Mendez, C (Taylor and Francis Ltd., 2022)
This investigation is the first to analyze how civil unrest impacts herding behavior in an emerging economy. Using series of prices and daily traded volumes of the companies that make up the IGPA of the Santiago Stock Exchange between 2010 and 2020, it was found that civil unrest causes reverse herding behavior in the Chilean stock market. Thus, herding behavior and inverse herding behavior are more complex behaviors than the financial literature has reported to date, especially in a period of civil unrest. Different robustness tests support the findings. © 2021 The Author(s). Published by Informa UK Limited, trading as Taylor & Francis Group.